Залежність структури і властивостей дифузійного силіційованого шару на сірому чавуні від складу суміші, що насичує - Кондрашова, С.Г.; Саприкін, Є.В.; Наумик, В.В.; Романенко, О.С.; Ченцова, А.О. (Physico-technological Institute of Metals and Alloys, 2023)
The article presents the results of studies on the selection of the optimal composition of the saturating mixture during silicification of gray cast iron. The work was carried out using the method of mathematical planning of the experiment. It was found that when saturated in mixtures with activators of NH4Cl and NH4F, with an increase in their percentage, the depth of the diffusion layer also increases. At the same time, a “fur coat” is formed on the samples, which leads to delamination of the diffusion layer, a decrease in the size of the processed products and makes them unsuitable for use. Thus, the use of these activators in diffusion silicification is undesirable. When NaF and NaCl activators are used in a saturating mixture, the depth of the diffusion layer is significantly reduced, the porosity practically disappears, and the layers come out solid, without chips and a “fur coat”. When used as an activator of NH4F, the diffuse layer is less porous, but very brittle and easily breaks off. The silicide Fe3Si is formed on the surface, which is confirmed by the data of x-ray diffraction analysis. In the result of siliconizing using the NaF activator, the depth of the diffusion layer is significantly reduced, and at the same time, the porosity decreases. The using of activator consisting of NH4Cl and NaF in a 1:1 ratio provides an increase in the depth of the non-porous diffusion layer while improving its corrosion resistance. Their total content in the saturating mixture should not exceed 4 %. A further increase in the percentage of activators in the saturating mixture does not lead to a noticeable increase in the depth of the diffusion layer and does not increase its operational properties. The disadvantage of the process in this case is the limited ability to obtain the a-layer of significant thickness. A study was conducted with the combined use of activators of small and high activity. It was found that the best parameters of the layer were obtained using a mixture consisting of 2 % NaF and 2 % NH4F. In this case, a dense, non-porous layer was formed. According to x-ray diffraction analysis, the layer mainly consists of FeSi silicide (η-phase) and a-solid solution of silicon in iron.